A digital score of tumour‐associated stroma infiltrating lymphocytes predicts survival in head and neck squamous cell carcinoma. Issue 2 (24th November 2021) - Shaban, Muhammad; Raza, Shan E Ahmed; Hassan, Mariam; Jamshed, Arif; Mushtaq, Sajid; Loya, Asif; Batis, Nikolaos; Brooks, Jill; Nankivell, Paul; Sharma, Neil; Robinson, Max; Mehanna, Hisham; et al.
Abstract: The infiltration of T‐lymphocytes in the stroma and tumour is an indication of an effective immune response against the tumour, resulting in better survival. In this study, our aim was to explore the prognostic significance of tumour‐associated stroma infiltrating lymphocytes (TASILs) in head and neck squamous cell carcinoma (HNSCC) through an AI‐based automated method. A deep learning‐based automated method was employed to segment tumour, tumour‐associated stroma, and lymphocytes in digitally scanned whole slide images of HNSCC tissue slides. The spatial patterns of lymphocytes and tumour‐associated stroma were digitally quantified to compute the tumour‐associated stroma infiltrating lymphocytes score (TASIL‐score). Finally, the prognostic significance of the TASIL‐score for disease‐specific and disease‐free survival was investigated using the Cox proportional hazard analysis. Three different cohorts of haematoxylin and eosin (H&E)‐stained tissue slides of HNSCC cases ( n  = 537 in total) were studied, including publicly available TCGA head and neck cancer cases. The TASIL‐score carries prognostic significance ( p  = 0.002) for disease‐specific survival of HNSCC patients. The TASIL‐score also shows a better separation between low‐ and high‐risk patients compared with the manual tumour‐infiltrating lymphocytes (TILs) scoring by pathologists for both disease‐specific and disease‐free survival. A positive correlation of TASIL‐score with molecular estimates of CD8 + T cells was also found, which is in line with existing findings. To the best of our knowledge, this is the first study to automate the quantification of TASILs from routine H&E slides of head and neck cancer. Our TASIL‐score‐based findings are aligned with the clinical knowledge, with the added advantages of objectivity, reproducibility, and strong prognostic value. Although we validated our method on three different cohorts ( n  = 537 cases in total), a comprehensive evaluation on large multicentric cohorts is required before the proposed digital score can be adopted in clinical practice. © 2021 The Authors. The Journal of Pathology published by John Wiley & Sons Ltd on behalf of The Pathological Society of Great Britain and Ireland.